2020
DOI: 10.1111/birt.12516
|View full text |Cite
|
Sign up to set email alerts
|

Rural resilience: The role of birth centers in the United States

Abstract: Purpose To explore the role of the birth center model of care in rural health and maternity care delivery in the United States. Methods All childbearing families enrolled in care at an American Association of Birth Centers Perinatal Data RegistryTM user sites between 2012 and 2020 are included in this descriptive analysis. Findings Between 2012 and 2020, 88 574 childbearing families enrolled in care with 82 American Association of Birth Centers Perinatal Data RegistryTM user sites. Quality outcomes exceeded na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Addressing inconsistencies in licensing of and reimbursement for out-of-hospital birth would improve preparation for future pandemics. [41][42][43] The lack of system flexibility contributes to this study's finding of increased work hours and increased patient volume among some respondents, and decreased work hours and patient volume among others. Although the reduction in elective services was a temporary change, the furloughing of employees and closing of private practices during the pandemic may reduce both access to care and the size of the workforce over a longer term.…”
Section: Discussionmentioning
confidence: 89%
“…Addressing inconsistencies in licensing of and reimbursement for out-of-hospital birth would improve preparation for future pandemics. [41][42][43] The lack of system flexibility contributes to this study's finding of increased work hours and increased patient volume among some respondents, and decreased work hours and patient volume among others. Although the reduction in elective services was a temporary change, the furloughing of employees and closing of private practices during the pandemic may reduce both access to care and the size of the workforce over a longer term.…”
Section: Discussionmentioning
confidence: 89%
“…Among the studies at AABC sites that matched similar cohorts from national data, breastfeeding rates were significantly higher at AABC sites (Alliman et al, 2019;Jolles et al, 2017). Although not everyone receiving perinatal care at an AABC site birthed at a birth center, the higher Jolles et al, 2017Jolles et al, , 2020Perdion et al, 2013;Thornton et al, 2017). Three studies described data about breastfeeding rates 4 to 6 weeks postpartum (Alliman et al, 2019;Nethery et al, 2021;.…”
Section: Discussionmentioning
confidence: 99%
“…Low intervention rates in labour and birth are also found in other remote settings [ 13 ]. Evidence from Canada demonstrated that rural maternity services may improved population health outcomes more than centralisation of maternity services [ 4 , 49 , 50 ]. Lower rates of preterm birth and low birth weight are found when women are provided with continuity of midwifery care in remote areas [ 8 , 51 ].…”
Section: Discussionmentioning
confidence: 99%